Kesantunan Berbahasa Masyarakat dan Pengunjung di Wisata Hiu Paus Desa Botubarani - Dali, Meilina Widya; Helingo, Aflah M A; Usman, Moh. Iftha; Rainusi, Fera Marta; Tahir, Harianti; Moha, Nazlya; Djafar, Safitri M; Arbi, Siti Juliyanti; Mutalib, Siti Nur Atira; Atulzanah, Siti Zahramar; Tahir, Uminarti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Linguistic politeness plays a crucial role in building social interactions, particularly in tourist areas that bring together local communities and tourists from diverse cultural backgrounds. The whale shark tourism area in Botu Barani Village is one such space where intense interactions occur. This article aims to examine the forms of linguistic politeness displayed by local residents and visitors, as well as the factors that influence them. This research uses a qualitative descriptive method through observation of social interactions and a literature review. The results indicate that the people of Botu Barani Village generally employ polite, friendly, and persuasive speech as part of their tourism services. Meanwhile, most visitors also demonstrate polite language, although some instances of language use are not in line with local norms. Overall, linguistic politeness has been shown to contribute significantly to creating a safe, comfortable, and harmonious tourism atmosphere.